Assessment of 8-hydroxydeoxyguanosine levels in patients with preeclampsia: A prospective study - Akıncı, Sezen; Özcan, Hüseyin Çağlayan; Balat, Özcan; Uğur, Mete Gürol; Öztürk, Ebru; Taysi, Seyithan; Sucu, Seyhun (7847050 Canada Inc, 2017)
Purpose of investigation: To determine the levels of 8-hydroxydeoxyguanosine (8-OHdG) in preeclampsia (PE) using (enzyme linked immunosorbent assay (ELISA) method. Materials and Methods: Twenty-two pregnant women with severe PE, 18 pregnant women with mild PE, and 40 healthy pregnant women, all between 25 and 41 weeks of gestation, were enrolled in this prospective controlled study. 8-OHdG levels in maternal serum were measured using ELISA method. Results: The authors observed no statistically significant difference in 8-OHdG levels between the mild-severe PE and control groups (p = 0.208). Conclusion: The present results do not support the concept that 8-OHdG has a role in the etiopathogenesis of PE.
WOS: 000396801700013
PubMed ID: 29746027
Keywords: Oxidative Stress; Preeclampsia; 8-Hydroxydeoxyguanosine